Determination of Wave Length of Heliy-Neon Laser Light Using Michacelson Interferometer - Abdurasulovna, Oyimxol Niyozova (European Journal of Life Safety and Stability (2660-9630), 2021)
We can use a Michelson interferometer to observe interference and determine the wavelength of helium-neon laser light in the experimental classes of optics.